Learning evaluation in the capabilities approach in higher education: a systematic review - Castro Córdova, Delsa Esther (2025)
The article presents the results of a systematic review on the assessment of learning from the capability approach in higher education. The identified problem lies in the fact that, although higher education curricula—including teacher education—declare the adoption of this approach, the assessment practices applied to students are not always consistent with its principles. In this context, the objective of the study was to identify the characteristics of the capability approach that are considered in learning assessment within higher education institutions. The review was conducted through a systematic search of academic databases and the Information System on Educational Trends in Latin America (SITEAL), which made it possible to identify relevant gaps in the literature, particularly regarding the theoretical and practical articulation between learning assessment and the capability approach. Nevertheless, convergences were found around emerging assessment practices, such as formative assessment, aimed at valuing student autonomy, diversity, and critical thinking. These practices reflect, albeit implicitly, fundamental principles of the capability approach, such as freedom, dignity, and respect for individual contexts.The methodological process followed the PRISMA statement and was supported by Rayyan, ResearchRabbit, and Atlas.ti for the selection, organization, and qualitative analysis of the included studies. It is concluded that there is a need to move toward assessment models consistent with higher education centered on human development, equity, and social justice.